Determination of Customer Loyalty in the International Cargo Company - Olfebri Olfebri (Dinasti Publisher, 2024)
The purpose of this research is to understand the Factors Influencing Customer Loyalty: This study probably aims to investigate the factors that most influence customer loyalty in the freight forwarding sector. This can include aspects such as the relationship between the company and customers, service quality, customer satisfaction, price, and other relevant factors and measure the level of customer loyalty to freight forwarding companies in East Jakarta. This can be done through surveys, interviews, or analysis of historical data. The study used quantitative methods, which used random sampling for respondents to find data, the population is a user of freight forwarders in the East Jakarta Area by disseminating online and directly. Data analysis was processed using SEM PLS series 4 to find a definite answer from the results of the questionnaire distribution that lasted for two months. In this study, only the relationship between relationship and customer loyalty showed statistical significance, but the direction of the relationship did not match initial predictions. The relationship between Customer Satisfaction and Customer Loyalty has not been shown to be statistically significant. Recommendations in the freight forwarding sector, increasing customer loyalty can be achieved through improved customer relationships, consistent service quality, and ensuring customer satisfaction. By focusing on these aspects, companies can strengthen long-term relationships with customers and improve their performance in the freight forwarding industry